Pengaruh Transformasi Digital terhadap Peningkatan Daya Saing Usaha Mikro, Kecil, dan Menengah (UMKM) di Era Ekonomi Digital - Rayvaldo Rayvaldo (CV. SINAR HOWUHOWU, 2026)
Digital transformation has become an important strategy for enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the digital economy era. This study aims to analyze the effect of digital transformation on improving MSME competitiveness. The research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 120 MSME owners who had adopted digital technologies in their business activities. The sampling technique used was purposive sampling, while data analysis was conducted using descriptive statistics and simple linear regression with the assistance of SPSS software. The results indicate that both digital transformation and MSME competitiveness are categorized as high. Digital transformation has a positive and significant effect on MSME competitiveness, with a significance value of 0.000 (< 0.05) and a coefficient of determination (R²) of 0.568. The findings demonstrate that digital transformation enhances operational efficiency, expands market reach, promotes product innovation, and strengthens customer relationships. Therefore, digital transformation can serve as a strategic factor in improving the competitiveness and sustainability of MSMEs in the digital economy era.